«Happy as a dog»: the reception of Diogenes the Cynic in the poetry of Jorge Guillén (Minerva, 2020)
In this paper, a manifestation of the Classical reception in the poet Jorge Guillén (1893-1984) is analyzed: his poem “Diógenes”, belonging to the poem-book Final (1981). This poem is a thorough survey of the Cynic poet and covers the following aspects: 1) The figure of Diogenes (ll. 1-5, 38-39); 2) Doctrine and attitudes (6-30); and 3) Death of the philosopher (31-37). His main source for documentation, although not the only one, was The Lives of Illustrious Poets by Diogenes Laertius. The modern poet underlines the following traits of the ancient philosopher: his shamelessness, his search for complete freedom of speech, the need of both physical and spiritual exercise, his joy of life, and his preference for a simple life. It is concluded that Jorge Guillén evocates the figure of Diogenes as an objective correlative to express his own values.
Keywords: Jorge Guillén; Diogenes; Cynicism; classical reception; hypotext; hypertext